UPAYA PENINGKATAN HASIL BELAJAR PPKN MELALUI PENERAPAN MODEL PEMBELAJARAN LISTENING TEAMS DI KELAS VIII SMP NEGERI 1 O’O’U TAHUN PEMBELAJARAN 2022/2023 - Jhon Keinelling Laia (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2023)
The learning process tends to be centered on the teacher, students do not understand the lesson because the learning model used by the teacher is not appropriate, so what is done by applying the Listening Teams learning model can change the learning system which has tended to be monotonous so far, to become more active in learning. This study aims to determine efforts to improve student learning outcomes in Pancasila and Citizenship Education subjects through the application of the Listening Teams learning model in class VIII SMP Negeri 1 O'o'u 2022/2023 Academic Year. This research uses the type of Classroom Action Research. The research subjects were 27 grade VIII students. Student learning outcomes show that in the first cycle of 62.96% and the second cycle increased to 100%. The average value of cycle I was 63 and increased in cycle II to 78. The conclusion of the study was that through the application of the Listening Teams learning model, student learning outcomes were obtained in the subject of Pancasila and Citizenship Education in class VIII SMP Negeri 1 O'o'u 2022 Academic Year /2023. The researcher gave several suggestions, namely: Schools, especially Pancasila and Citizenship Education subject teachers, should pay attention to learning models, which vary and are adapted to the subject matter being taught. The Listening Teams learning model should be applied to each subject because this learning model requires the activity of students as a whole. Develop further research with longer time planning so that the research results obtained are more optimal and effective.